2016
DOI: 10.18632/oncotarget.6675
|View full text |Cite
|
Sign up to set email alerts
|

The long noncoding RNA MALAT1 promotes tumor-driven angiogenesis by up-regulating pro-angiogenic gene expression

Abstract: Neuroblastoma is the most common solid tumor during early childhood. One of the key features of neuroblastoma is extensive tumor-driven angiogenesis due to hypoxia. However, the mechanism through which neuroblastoma cells drive angiogenesis is poorly understood. Here we show that the long noncoding RNA MALAT1 was upregulated in human neuroblastoma cell lines under hypoxic conditions. Conditioned media from neuroblastoma cells transfected with small interfering RNAs (siRNA) targeting MALAT1, compared with condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(80 citation statements)
references
References 29 publications
4
75
0
1
Order By: Relevance
“…Metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) is another lncRNA, which plays an essential role in angiogenesis [39]. MALAT1 is significantly upregulated by hypoxia and hyperglycemia in endothelial cells [40].…”
Section: Lncrna and Angiogenesismentioning
confidence: 99%
“…Metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) is another lncRNA, which plays an essential role in angiogenesis [39]. MALAT1 is significantly upregulated by hypoxia and hyperglycemia in endothelial cells [40].…”
Section: Lncrna and Angiogenesismentioning
confidence: 99%
“…57 Hypoxia could promote angiogenesis of ECs through vascular endothelial growth factor (VEGF) signaling and also induce expression of MALAT1. [58][59][60][61] MALAT1 knockdown significantly reduced the VEGF expression and the capacity for angiogenesis via inhibition of 15-lipoxygenase 1 (15-LOX1) and the phosphorylation of signal transducers and activators of transcription 3 (pSTAT3). 17…”
Section: Malat1 and Angiogenesismentioning
confidence: 99%
“…As one of the first identified cancerā€associated lncRNAs, MALAT1 was reported to be overexpressed in gastric cancer (Chen, Liu, Wang et al, 2017), breast cancer (Arun et al, ), prostate cancer (Ren et al, ), cervical cancer (Sun, Qin et al, ), acute myeloid leukemia (Chen, Nagel et al, 2018), medullary thyroid cancer (Chu, Hardin, Schneider, Chen, & Lloyd, ), choriocarcinoma (Shi, Wang, & Yin, ), gallbladder cancer (Sun et al, ), pancreatic cancer (Xie et al, 2017), multiple myeloma (Liu, Wang et al, ), ovarian cancer (Wu et al, 2017), T and natural killer cell lymphoma (Kim, Kim, Yang, Kim, & Yoon, ), acute monocytic leukemia (Huang, Liu et al, ), endometrial stromal sarcoma (Yamada et al, ), myeloma (Cho et al, ), clear cell renal cell carcinoma (Zhang, Yang, Chen, Che, & Zheng, ), esophageal squamous cell carcinoma (Hu et al, ), glioma (Ma, Wang, Li et al, ), osteosarcoma (Cai et al, ), neuroblastoma (Tee et al, ), tongue squamous cell carcinomas (Fang et al, ), hilar cholangiocarcinoma (Tan, Huang, & Li, ), mantle cell lymphoma (Wang, Zhu et al, ), and other tumor tissues. It has been reported that MALAT1 is involved in the regulation of tumor proliferation, apoptosis, invasion, metastasis, and angiogenesis.…”
Section: Physiopathological Role Of Malat1mentioning
confidence: 99%